The effect of a healthy nutritional program on body mass index and anthropometric measurements in obese women - Tuaimah, Mohammed Hasan; Kuswoyo, Dilli Dwi (Jurnal Ilmu Keolahragaan, 2025)
Background. Overweight and obesity represent significant health challenges in contemporary society, particularly during periods of stunted physical development and hormonal imbalance. These conditions increase the risk of serious health issues, including coronary heart disease and high blood pressure. Addressing these problems through non-invasive and sustainable approaches is crucial, particularly among women. Objectives. This study aims to design a physical nutrition program incorporating circuit training to promote weight loss in women. Specifically, it seeks to determine the program"™s impact on body weight, body mass index (BMI), and the circumferences of selected body parts. Methods. The research utilized a pre-test and post-test experimental design. A tailored physical and nutritional program was applied to the study participants, and measurements were taken for body weight, BMI, and morphological circumferences of specific body areas before and after the intervention. The differences between pre- and post-test results were analyzed statistically to assess the program's effectiveness. Results. The findings revealed statistically significant improvements in all measured variables in favor of the post-test. The program contributed to a marked reduction in body weight, BMI, and the circumferences of various body parts. The magnitude of the program"™s impact followed the order: BMI, body weight, and body circumferences. Conclusion The proposed physical and nutritional program demonstrated a positive effect on weight loss and body composition among women. It offers a practical, non-surgical alternative to weight management and highlights the importance of integrating exercise with nutrition to achieve optimal results. The study recommends adopting such integrated programs to enhance women's health and physical well-being.